2021
DOI: 10.1007/s11356-021-17243-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation assessment of RB5 dye by utilizing WO3/TiO2 nanocomposite: a cytotoxicity study

Abstract: Textile dyeing wastewater becomes one of the root causes of environmental pollution. Titanium dioxide (TiO 2 ) is one of the photocatalysts that shows prominent organic dye photodegradation ability. In this study, a porous tungsten oxide (WO 3 )/ TiO 2 composite was prepared through ultrasonic-assisted solvothermal technique with varying amounts of WO 3 ranging from 0.25 to 5 weight % (wt.%). The prepared 0.50 wt.% WO 3 /TiO 2 (0.50WTi) composite exhibited the highest photodegradation activity (4.39 × 10 −2 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Photocatalysis is a chemical reaction that happens in the interaction between light and a photocatalyst. Due to its efficacy and adaptability, photocatalytic degradation has become an increasingly attractive solution for water pollution concerns [3][4]. Photocatalysts are a favorable method in treating dirty water and textile waste.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photocatalysis is a chemical reaction that happens in the interaction between light and a photocatalyst. Due to its efficacy and adaptability, photocatalytic degradation has become an increasingly attractive solution for water pollution concerns [3][4]. Photocatalysts are a favorable method in treating dirty water and textile waste.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In photocatalytic method, 63% and 23% of RB5 was degraded by immobilized TiO2 within 5 hours for initial dye concentration of 55 and 110 µmol/ dm 3 , respectively. By combining the two methods, the researchers concluded that the concentration of the dye and TOC was effectively reduced 24 . In another study, Chengyuan and his coworkers 25 studied effect of cephalexin after heterogeneous Fenton-like pretreatment on the performance of anaerobic granular sludge and activated sludge.…”
Section: Introductionmentioning
confidence: 99%